The Impact of AI-Powered Software on Second Language (L2) Writing: A Systematic Literature Review - ROA, Angela Andrea Perez; HALIM, Shanty (Politeknik Negeri Ujung Pandang, 2024)
The utilization of artificial intelligence (AI)-powered tools in second language (L2) writing has evolved over the last decade. This attracted second-language writers to evaluate and improve their writing. This study aims to contribute to the understanding of the current state of AI-powered software in L2 writing, identify gaps in the literature, and investigate areas for future research. In this systematic literature review (SLR), we categorize the typology of AI-powered tools and their impact on L2 writing performance, discuss L2 writers' perceptions, and provide an overview of how they mitigate challenges and limitations in utilizing writing-assisted tools. The results of this SRL may have implications for writing teachers, L2 researchers, and developers of AI-powered writing tools in the field of second language writing.